(untitled) (World Bulletin of Public Health, 2024)
Currently, a large number of studies are devoted to the study of polymorphisms of various genes in patients with coronary heart disease (CHD). The study of some of them, for example, genes of the blood coagulation system, has revealed some contradictions or vice versa patterns and deserves further consideration.